الفهرس الموحد للمکتبات المدرسیة المصریة :دراسة حالة - د. عبد الرحیم محمد عبد الرحیم (المجلة الدولية لعلوم المكتبات والمعلومات)
The study aimed to analyses and evaluate the union catalog in theschool libraries in Egypt, and recognizing its perception’s degree, and itscomprehension for the resources that the libraries have, and defining theproblems and the obstacles that face the librarians in preparing the unioncatalog for school libraries in Egypt and by the case study method I’vereached with the study lots of results and the more important ones of themis that the common schools libraries have reached 2.19% of the total of theEgyptian governmental schools in preparing the union catalog, and theinvolved institutes reached 2.29% only of the total of the AZHAR’sinstitutes in preparing the union catalog due to, that there’s no legal, formalform for the schools libraries corpus Egypt, and there’s also the work withthe union catalog gests done depending on the volunteers’ effort.